2021
DOI: 10.1016/j.infpip.2021.100122
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene: virucidal efficacy of a liquid hand wash product against Ebola virus

Abstract: Summary Background Hand washing is an important targeted hygiene intervention for limiting the spread of infectious agents, including the Ebola virus, which continues to re-emerge. We have assessed the virucidal efficacy of a commercially available liquid hand wash product (LHW) for inactivating Ebola virus. Methods The ASTM E1052-11 Standard was used to evaluate the efficacy of an LHW containing the microbicidal active salicylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Mencuci tangan merupakan intervensi kebersihan yang ditargetkan untuk membatasi penyebaran agen infeksi. (Cutts et al, 2021) Dengan membiasakan mencuci tangan dengan sabun dapat meminimalkan terjadinya diare hingga 50 persen. (Misroh & Abdul, 2021).…”
Section: Pendahuluanunclassified
“…Mencuci tangan merupakan intervensi kebersihan yang ditargetkan untuk membatasi penyebaran agen infeksi. (Cutts et al, 2021) Dengan membiasakan mencuci tangan dengan sabun dapat meminimalkan terjadinya diare hingga 50 persen. (Misroh & Abdul, 2021).…”
Section: Pendahuluanunclassified
“…Lipid envelope-disrupting hand wash agents, as a class, appear to display efficacy after relatively short contact times. For instance, Ogilvie et al (2020) found that QAC-based products inactivated SAR-CoV-2 in various soil loads within 15 s. Lavelle et al (1989) showed that exposure to a hand wash product containing the phenolic p -chloro- m -xylenol caused concentration-dependent inactivation of human immunodeficiency virus ( Retroviridae ) suspended within a blood matrix within 30 s. The inactivation of Ebola virus Makona variant ( Filoviridae ) within a tripartite soil load (bovine serum albumin, tryptone, and bovine mucin) by a liquid hand wash agent also displayed concentration-dependent inactivation within 20 s contact time ( Cutts et al, 2020a ). Furthermore, disinfectant pre-impregnated wipes containing activated hydrogen peroxide or QAC have been shown to inactivate Ebola virus Makona variant and vesicular stomatitis virus ( Rhabdoviridae ) after a 5-s contact time ( Cutts et al, 2020b ).…”
Section: Why Is Adherence To the Recommended Contact Time So Critical?mentioning
confidence: 99%
“…Lavelle et al (1989) showed that exposure to a hand wash product containing the phenolic pchloro-m-xylenol caused concentration-dependent inactivation of human immunodeficiency virus (Retroviridae) suspended within a blood matrix within 30 seconds. The inactivation of Ebola virus Makona variant (Filoviridae) within a tripartite soil load (bovine serum albumin, tryptone, and bovine mucin) by a liquid handwash agent also displayed concentration-dependent inactivation within 20 seconds contact time (Cutts et al, 2020a). Furthermore, disinfectant preimpregnated wipes containing activate hydrogen peroxide or QAC have been shown to inactivate Ebola virus Makona variant and vesicular stomatitis virus (Rhabdoviridae) after a 5-second contact time Cutts et al, 2020b).…”
Section: Why Is Adherence To the Recommended Contact Time So Critical?mentioning
confidence: 99%